Penerapan Metode Forward Chaining untuk Mendiagnosa Penyakit Tanaman Sawi - Ajeng Savitri Puspaningrum; Erliyan Redy Susanto; Adi Sucipto (Faculty of Computer Science, University of Jember, 2020)
Mustard greens is one of the plants that is very susceptible to disease. There is no type of mustard greens plant that is strong against disease or pests. In order to overcome or treat these diseases and pests, mustard greens farmers need to know the type of disease or pest that is attacking. But unfortunately, farmers' knowledge regarding mustard plant diseases is limited to the visible symptoms or the condition of the affected plant. The lack of knowledge of mustard greens farmer practitioners is due to the lack of counseling so that the presence of experts to help farmers is needed. Unfortunately, the experts are not always able to help if the condition requires fast handling because the number of experts are not many. In this study, this problem was resolved by developing a system equivalent to expert knowledge in detecting diseases in mustard plants. The system developed was a web-based system to detecting types of mustard disease automatically with the forward chaining method which can be used as an alternative to manual activities carried out by experts using 9 pests/diseases and 18 symptoms. The test results showed that the level of accuracy with expert expertise reaches 88.8%